Perspektif Bioetika Terhadap Penggunaan Data Genomik dalam Riset Personalized Medicine - Telaumbanua, Titi Krisnawati; Zega, Perlindungan; Waruwu, Jernih Puspita Sari; Zega, Novelina Andriani (Indo-MathEdu Intellectuals Journal, 2026)
Advances in genome sequencing technology have opened significant opportunities for the development of personalized medicine, but have also given rise to ethical complexities that require in-depth study. This study aims to identify and analyze key bioethical issues arising from the use of genomic data for personalized medicine research through a critical-normative literature review. A thematic analysis of the selected literature identified four key bioethical domains: autonomy and informed consent in the context of complex genomic data, privacy and data security facing the risks of leaks and misuse, fairness in access to genomic services, and the potential for genetic discrimination. Findings indicate that implementing the principle of autonomy faces technical challenges in conveying comprehensible information, while privacy issues require inadequate regulatory frameworks in many countries. Genetic discrimination in the context of insurance and employment poses a real threat that requires explicit legal protection. This study recommends the development of an integrative bioethical framework that connects classical ethical principles with the realities of genomic technology, strengthening genomic data protection regulations, and adapting informed consent mechanisms. Policy implications include the urgency of harmonizing regulations across countries and strengthening the capacity of research ethics committees to evaluate genomic research protocols